Determination of Structural and Optical Properties of Zn1-xCuxO Nanoparticles by Chemical Bath Deposition Waste Recovery Technique - Emin Yakar (Journal of Advanced Research in Natural and Applied Sciences)
In this work, Zn1-xCuxO nanoparticles (x= 0.025, x=0.050, and x=0.075) were synthesized by co-precipitation technique using chemical bath deposition wastes of Cu:ZnO thin films. The XRD evaluation showed that the well-crystalline hexagonal wurtzite ZnO indexed peaks. Average crystallite sizes were found to be around 35.6-42.9 nm range by using the Debye-Scherrer equation. Surface morphology results showed that dense layer of nano-roses and fewer nanorods formations in low Cu-concentrated (x=0.025 and x=0.050) samples. The optical absorption edge shifted slightly to the higher wavelength from 350 nm to 375 nm with decreasing copper concentration, as mentioned the blue shift. Blue shift might be caused an increase in the optical band gap from 3.14 eV to 3.28 eV due to the decrease in Cu concentration.